In the Light of Evolution: Volume IV: The Human Condition - National Academy of Sciences (The National Academies Press, 2010)
The Human Condition is a collection of papers by leading evolutionary biologists and philosophers of science that reflect on the Darwinian Revolution as it relates to the human condition at levels ranging from the molecular to the theological. The book focuses on understanding the evolutionary origin of humans and their biological and cultural traits. The Human Condition is organized into three parts: Human Phylogenetic History and the Paleontological Record; Structure and Function of the Human Genome; and Cultural Evolution and the Uniqueness of Being Human. This fourth volume from the In the Light of Evolution (ILE) series, based on a series of Arthur M. Sackler colloquia, was designed to promote the evolutionary sciences. Each volume explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. Individually and collectively, the ILE series interprets phenomena in various areas of biology through the lens of evolution, addresses some of the most intellectually engaging as well as pragmatically important societal issues of our times, and fosters a greater appreciation of evolutionary biology as a consolidating foundation for the life sciences.
Keywords: Biology and Life Sciences

Forging the Future of Space Science: The Next 50 Years - National Research Council (The National Academies Press, 2010)
From September 2007 to June 2008 the Space Studies Board conducted an international public seminar series, with each monthly talk highlighting a different topic in space and Earth science. The principal lectures from the series are compiled in Forging the Future of Space Science. The topics of these events covered the full spectrum of space and Earth science research, from global climate change, to the cosmic origins of life, to the exploration of the Moon and Mars, to the scientific research required to support human spaceflight. The prevailing messages throughout the seminar series as demonstrated by the lectures in this book are how much we have accomplished over the past 50 years, how profound are our discoveries, how much contributions from the space program affect our daily lives, and yet how much remains to be done. The age of discovery in space and Earth science is just beginning. Opportunities abound that will forever alter our destiny.
Keywords: Space and Aeronautics

Ecosystem Concepts for Sustainable Bivalve Mariculture - National Research Council (The National Academies Press, 2010)
U.S. mariculture production of bivalve molluscs-those cultivated in the marine environment-has roughly doubled over the last 25 years. Although mariculture operations may expand the production of seafood without additional exploitation of wild populations, they still depend upon and affect natural ecosystems and ecosystem services. Every additional animal has an incremental effect arising from food extraction and waste excretion. Increasing domestic seafood production in the United States in an environmentally and socially responsible way will likely require the use of policy tools, such as best management practices (BMPs) and performance standards. BMPs represent one approach to protecting against undesirable consequences of mariculture. An alternative approach to voluntary or mandatory BMPs is the establishment of performance standards for mariculture. Variability in environmental conditions makes it difficult to develop BMPs that are sufficiently flexible and adaptable to protect ecosystem integrity across a broad range of locations and conditions. An alternative that measures performance in sustaining key indicators of ecosystem state and function may be more effective. Because BMPs address mariculture methods rather than monitoring actual ecosystem responses, they do not guarantee that detrimental ecosystem impacts will be controlled or that unacceptable impact will be avoided. Ecosystem Concepts for Sustainable Bivalve Mariculture finds that while performance standards can be applied for some broad ecosystem indicators, BMPs may be more appropriate for addressing parameters that change from site to site, such as the species being cultured, different culture methods, and various environmental conditions. This book takes an in-depth look at the environmental, social, and economic issues to present recommendations for sustainable bivalve mariculture.
Keywords: Earth Sciences; Environment and Environmental Studies; Agriculture